2018
DOI: 10.1509/jm.15.0481
|View full text |Cite
|
Sign up to set email alerts
|

Design Crowdsourcing: The Impact on New Product Performance of Sourcing Design Solutions from the “Crowd”

Abstract: The authors examine an increasingly popular open innovation practice, “design crowdsourcing,” wherein firms seek external inputs in the form of functional design solutions for new product development from the “crowd.” They investigate conditions under which managers crowdsource design and determine whether such decisions subsequently boost product sales. The empirical analysis is guided by qualitative insights gathered from executive interviews. The authors use a novel data set from a pioneering crowdsourcing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(54 citation statements)
references
References 51 publications
(60 reference statements)
0
44
0
Order By: Relevance
“…Traditionally, products are designed by professionals who work for the firm and have expertise that allows them to perform design tasks at a high level of quality (Schreier, Fuchs, and Dahl 2012; Ulrich 2011). However, several studies have shown evidence that under certain conditions, consumers prefer user-designed products (Allen, Chandrasekaran, and Basuroy 2018; Dahl, Fuchs, and Schreier 2015; Fuchs and Schreier 2011; Nishikawa et al 2017; Schreier, Fuchs, and Dahl 2012). This line of research finds user-design approaches to be more innovative and customer oriented, and these approaches also increase consumers’ feelings of identification and empowerment.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, products are designed by professionals who work for the firm and have expertise that allows them to perform design tasks at a high level of quality (Schreier, Fuchs, and Dahl 2012; Ulrich 2011). However, several studies have shown evidence that under certain conditions, consumers prefer user-designed products (Allen, Chandrasekaran, and Basuroy 2018; Dahl, Fuchs, and Schreier 2015; Fuchs and Schreier 2011; Nishikawa et al 2017; Schreier, Fuchs, and Dahl 2012). This line of research finds user-design approaches to be more innovative and customer oriented, and these approaches also increase consumers’ feelings of identification and empowerment.…”
Section: Conceptual Framework and Hypothesesmentioning
confidence: 99%
“…“Crowdsourcing,” a more popular term to describe what is defined in the literature as “user-driven design,” is a successful innovation approach in which users create value alongside the firm (Dahl, Fuchs, and Schreier 2015; Schreier, Fuchs, and Dahl 2012; Von Hippel 2005). Research has found that nonparticipating users, or those who only observe and learn about a firm’s design philosophy (user design vs. company design), view user-design approaches as more innovative and customer oriented, leading to positive evaluations (Allen, Chandrasekaran, and Basuroy 2018; Fuchs and Schreier 2011; Nishikawa et al 2017; Schreier, Fuchs, and Dahl 2012). Other research has shown that user-design approaches increase identification with the firm through feelings of vicarious empowerment (Dahl, Fuchs, and Schreier 2015).…”
mentioning
confidence: 99%
“…Nonetheless, general crowdsourcing suffers from two flaws previously discussed: the mythical average and the static account of users. External input from the crowd on design solutions for new product development has been proven to positively influence sales and perceived reliability and usability (Allen, Chandrasekaran, & Basuroy, 2018). However, unless a conscious effort is made to increase the participation among broader consumer groups, the process is only good for generating ideas for the most served consumers.…”
Section: Future Research Directionsmentioning
confidence: 99%
“…Enabled by the platform, the consumer can get directly in touch with other consumers as well, exchanging ideas and values. Therefore, the consumer is not a single individuum on the market anymore, but part of the crowd, which is, for example, helping with design solutions of a product (Allen et al 2018). Danish toy manufacturer LEGO, amongst other companies, is applying this approach (Antorini et al 2012).…”
Section: Introductionmentioning
confidence: 99%